2009
DOI: 10.1155/2009/298381
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Bulb Mucosa with Hypertrophic Gastric Oxyntic Heterotopia in Patients with Zollinger Ellison Syndrome

Abstract: Objectives. Zollinger-Ellison Syndrome (ZES) results in hypersecretion of gastric acid (via gastrinoma) leading to peptic ulcers, diarrhea, and abdominal pain. We describe the novel discovery of hypertrophic, heterotopic gastric mucosa in the proximal duodenal bulb in patients with ZES, which we hypothesize results in an increased incidence of postbulbar ulcers in patients with ZES (a mechanism previously unreported). We determined the incidence of the novel finding of duodenal gastric oxyntic hypertrophic het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
1
4
0
Order By: Relevance
“…One study demonstrated that patients with gastric oxyntic heterotopia found in the duodenum had increased serum gastrin levels [16]. Our patient's duodenal mass histology indeed demonstrated oxyntic gastric glandular cells.…”
Section: Discussionsupporting
confidence: 60%
“…One study demonstrated that patients with gastric oxyntic heterotopia found in the duodenum had increased serum gastrin levels [16]. Our patient's duodenal mass histology indeed demonstrated oxyntic gastric glandular cells.…”
Section: Discussionsupporting
confidence: 60%
“…It can be found anywhere in the gastrointestinal (GI) tract [ 6 ]. GH in the duodenum is a benign condition and the incidence is reported to vary from 0.5 to 14%, although in the duodenal bulb, it is seen in only 0.5 to 2% of the general population [ 3 , 4 ]. Initial cases in the duodenum were identified on autopsies in a case series in 1927 [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…It can be found throughout the gastrointestinal (GI) tract and usually occurs in the form of polyps, nodules, or tumorous growths [ 1 - 3 ]. In the duodenum, GH is most commonly seen in the duodenal bulb in the form of multiple polyps in approximately 0.5 to 2% of the general population [ 2 , 4 ]. It has characteristic endoscopic and pathologic findings that are often mistaken for gastric metaplasia [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…VIP) that would be normally present when the antrum is contiguous with the gastric body. 8 In addition, the isolated antrum is exposed to the neutral or alkaline environment of the duodenum thus promoting acid formation. The BAO and MAO are elevated as in ZES, although the increase in baseline serum gastrin is moderate in comparison (usually < 1000 pg/ml).…”
Section: Introductionmentioning
confidence: 99%
“…The BAO and MAO are elevated as in ZES, although the increase in baseline serum gastrin is moderate in comparison (usually < 1000 pg/ml). 8 99m Tc scanning is the imaging modality of choice when suspecting the diagnosis of retained antrum; management includes antral resection and vagotomy.…”
Section: Introductionmentioning
confidence: 99%